PHARMACOKINETIC STUDY OF KETOPROFEN IN HEALTHY SHEEP UNDER LOCAL CONDITIONS OF PAKISTAN - A. Ali; S. Afzal; M. Ashraf; S. Amin; A. Javeed; M. Usman (Journal of Animal and Plant Sciences, 2012)
Pharmacokinetic of ketoprofen was studied in sheep after a single intravenous dose of 3mg/kg body mass. Blood samples were collected before and within 24 hours after drug administration. Plasma was separated immediately and concentration of ketoprofen at different time intervals were determined by validated HPLC method by using phosphate buffer pH:7.0 and acetonitrile (75:25) as mobile phase at wavelength of 254nm. Pharmacokinetic parameters were determined from the plasma concentration-time curves of by using two-compartment model. On average with ketoprofen, the area under curve (AUC) was 5.47±2.72h.mg/L, distribution half life (t½α) was 0.12±0.10h, elimination half life (t½β) was 1.91±0.95h, total body clearance (cl) was 0.65 ±0.25L/kg/h, steady state volume of distribution (vdss) was 0.82 ±0.46L/kg, maximum plasma concentration(Cmax) was 6.68±2.28mg/L and time to reach maximum concentration (Tmax) was 0.12±0.02h. Pharmacokinetic parameters showed that drug is rapidly eliminated from Pakistani sheep so dosage adjustment is required and dose should be higher than the recommended dose.
Keywords: Pharmacokinetics; Ketoprofen; High Performance liquid; Area under curve; Peak plasma concentration